A label-free fluorescent aptasensor for selective and sensitive detection of streptomycin in milk and blood serum. (15th July 2016) - Taghdisi, Seyed Mohammad; Danesh, Noor Mohammad; Nameghi, Morteza Alinezhad; Ramezani, Mohammad; Abnous, Khalil
Highlights: Streptomycin (STR), an antibiotic, is widely used in human and veterinary. Streptomycin could cause serious side effects on human. A fluorescent aptasensor was designed for detection of STR. This aptasensor showed excellent selectivity toward STR. The designed aptasensor was successfully used to detect STR in serum and milk. Abstract: Sensitive and fast detection of antibiotic residues in animal derived foods and blood serum is of great interest. In this study a fluorescent aptasensor was designed for selective and sensitive detection of streptomycin (STR) based on Exonuclease III (Exo III), SYBR Gold and aptamer complimentary strand. In the absence of STR, the fluorescence intensity is weak. Upon addition of STR, the aptamer binds to its target, leading to release of complementary strand from aptamer and more protection against Exo III function. Following addition of SYBR Gold, a strong fluorescence intensity is obtained. This aptasensor showed a high selectivity toward STR with a limit of detection (LOD) as low as 54.5 nM. The validity of the procedure and applicability of the aptasensor were successfully assessed by detection of STR in a spiked milk and blood serum without interference from the sample matrix.